An investigation of X-ray and radio isotope energy absorption of heavyweight concretes containing barite - Esen, Yuksel; Yilmazer, Berivan (Indian Acad Sciences, 2011)
This study investigated the X-ray and radioisotope energy absorption capacity of heavyweight concrete containing barite aggregate. Concrete plates were prepared using differing amounts of barite aggregate instead of normal aggregate. Density-thickness-energy variations of these concretes for 85 keV, 118 keV, 164 keV, 662 keV and 1250 keV ray energies were recorded. It was observed that the concretes with greater barite content had a higher density and energy absorption capacity.
Keywords: Barite; heavyweight concrete; radiation shielding; concrete